Blood and Sputum Eosinophils of COPD Patients Are Differently Polarized than in Asthma - Katarzyna Mycroft; Magdalena Paplińska-Goryca; Małgorzata Proboszcz; Patrycja Nejman-Gryz; Rafał Krenke; Katarzyna Górska (Cells, 2023)
Different eosinophil subpopulations have been identified in asthma and other eosinophilic disorders. However, there is a paucity of data on eosinophil subpopulations in patients with chronic obstructive pulmonary disease (COPD). The aim of this study was to compare eosinophil phenotypes in blood and induced sputum in patients with COPD, asthma and controls. Stable patients with mild-to-moderate COPD (n = 15) and asthma (n = 14) with documented blood eosinophilia ≥100 cells/µL in the year prior to the study and the control group (n = 11) were included to the study. The blood and sputum eosinophil phenotypes were analyzed by flow cytometry. IL-5, IL-13, CCL5 and eotaxin-3 levels were measured in the induced sputum. The marker expression on blood eosinophils was similar among control, asthma and COPD groups. The expressions of CD125, CD193, CD14 and CD62L were higher on blood than on sputum eosinophils in all three groups. We found increased levels of CD193+ and CD66b+ sputum eosinophils from COPD patients, and an elevated level of CD11b+ sputum eosinophils in asthma compared to COPD patients. The results of our study suggest that the profile of marker expression on COPD sputum eosinophils differed from other groups, suggesting a distinct phenotype of eosinophils of COPD patients than in asthma or healthy subjects.